Antibiotic Use in Pediatric Pharyngitis at Juanda Samarinda Public Health Center from January-December 2023 - -, Mardiana -; Geografi, Liniati; Simanullang, Raymon (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Pharyngitis is an infection or inflammation of the pharyngeal (throat) region, primarily caused by bacteria and viruses. The most common bacterial cause is Group A Streptococcus. Management of bacterial pharyngitis involves the use of antibiotics aimed at eradicating the causative pathogen. Quantitative analysis of antibiotic use can be conducted using the Defined Daily Dose (DDD) method, which is useful for assessing both the pattern and volume of drug consumption. This study aims to quantify the use of antibiotics in pediatric pharyngitis patients using the ATC/DDD method at Juanda Samarinda Public Health Center in 2023. This research is classified as a descriptive quantitative study and employs a non-experimental, retrospective design. Data were collected from antibiotic usage reports and medical records of pediatric pharyngitis patients treated in 2023. Data processing was performed using descriptive and quantitative analysis, with all results processed using Microsoft Excel 2019 and presented in tabular format. Based on the findings, the antibiotic with the highest usage in pediatric pharyngitis patients at Juanda Samarinda Public Health Center was Amoxicillin, with an average of 38.5 DDD/1,000 patient-days (KPRJ), while the lowest was Cefadroxil, with an average of 4.9 DDD/1,000 patient-days (KPRJ).